Dihydrofolate reductase mutations in Plasmodium vivax from Indonesia and therapeutic response to sulfadoxine plus pyrimethamine. - Hastings, MD; Porter, K; Maguire, J; Susanti, I; Kania, W; Bangs, M; Sibley, C; Baird, J (2004)
BACKGROUND: The target enzyme of pyrimethamine is dihydrofolate reductase (DHFR), but little is known about allelic variants of dhfr in Plasmodium vivax populations. Still less is known about associations between specific alleles and the failure of sulfadoxine/pyrimethamine (S/P) to clear the erythrocytic stages of P. vivax in vivo. METHODS: We studied P. vivax dhfr mutations in 24 patients who received S/P therapy in Papua or Central Java, Indonesia, and we measured the resistance of the alleles in vitro in a dhfr yeast expression assay. RESULTS: Fourteen (58%) of 24 patients had an inadequate therapeutic response. Two of 6 alleles that were identified were novel. One allele that expressed 4 point mutations (57L+58R+61M+117T) correlated with a high risk of therapeutic failure. The 9 patients infected by P. vivax carrying this allele proved 23 times more likely to experience early therapeutic failure, compared with patients infected by P. vivax carrying other alleles (P=.003; 95% confidence interval, 2-450). This allele also conferred high levels of pyrimethamine resistance in vitro. The experimental antifolate WR99210 inhibited the allele in this system. CONCLUSIONS: The present study identified a strong correlation between specific mutations in P. vivax dhfr and S/P treatment failure. Our results suggest that WR99210 could provide effective therapy for S/P-resistant P. vivax.